The meaning of a brand? An archetypal approach (REGE Revista de Gestão, 2018)
Abstract Purpose –The purpose of this paper is to analyze customers’ perceptions about brand personality in different cultural environments, checking if the archetypal framework of Mark and Pearson (2001) applies to different brands across countries. Design/methodology/approach – The authors measured consumers’ perceptions in different cultural contexts through a survey, and received 537 valid questionnaires from Portugal, Brazil, Colombia and Peru, countries that have some similar indicators of cultural proximity. The authors wanted to verify if the words and sentences that respondents related to each brand were coherent with the archetype/brand, and the homogeneity of the results in different cultural contexts. Findings – Empirical evidence shows that there is proximity between the literature review and the associations – words and sentences – that consumers from different countries make with those brands. This consistency of results is significantly higher for word associations. Originality/value – Regardless of the results, the perceptions of consumers expressed through the selected words were often diverse and heterogeneous among countries. This could possibly indicate insufficient efforts from global brands toward a coherent brand personality/global-archetypal approach. Therefore, managing brand personality deserves more attention and marketers must understand consumer behavior patterns in different markets.